O-025 Outcomes of rescue endovascular treatment of acute ischemic stroke in patients with underlying intracranial atherosclerosis – insights from star registry. (4th August 2020) - Al Kasab, S; Almallouhi, E; Maier, I; Arthur, A; Kim, J; De Leacy, R; Rai, A; Keyrouz, S; Fargen, K; Dumont, T; Kan, P; Starke, R; et al.
Abstract : Introduction: Mechanical Thrombectomy (MT) is the standard of care for patients presenting with emergent large vessel occlusion (ELVO) with salvageable tissue. A subgroup of ELVO is refractory to reperfusion due to underlying intracranial atherosclerosis (ICAS), often requiring rescue therapy with balloon angioplasty, stenting or both. Whether such rescue therapy is safe and effective remains to be established. The purpose of this study is to investigate the safety, efficacy, and long-term outcomes of MT for ELVO related ICAS. Methods: We queried the databases of 11 thrombectomy-capable centers in the US and Europe included in STAR (S troke T hrombectomy and A neurysm R egistry). In this analysis, we included patients who underwent rescue therapy (balloon angioplasty and/or stenting) in the setting of ELVO due to underlying ICAS. A matched sample was produced by matching on the variables of age, admission NIHSS, and location of the occlusion. Results: Out of 2827 thrombectomy patients included in STAR at the time of this analysis, 190 patients required rescue therapy for ELVO with underlying ICAS. Balloon angioplasty was performed on 116 patients, and 113 patients had intracranial stenting. On multivariate analysis, after controlling for age, sex, race, hypertension, diabetes, prior stroke, NIHSS on admission and location of occlusion; compared to angioplasty alone, or stenting alone, combination therapy with angioplasty and stenting was associated with higher odds of favorable long-term functional outcome (mRS 0–2) (OR 4.404, 95% CI 1.318–9.712; P=0.021).in the matched analysis, 161 rescue therapy patients matched to a similar number of controls. There was no difference in age, race, sex, rate of IV tPA administration, ASPECTS score, or onset to groin time. Successful first attempt rate was lower (52% vs. 22%, p=0.001) and procedural time was longer in the rescue therapy group (47 min vs. 31 min, p≤0.001). There was no difference in symptomatic intracranial hemorrhage (7.5% vs. 5.6%, p=0.49), or favorable long term functional outcome (modified Rankin scale 0–2) (42.2% vs. 50.9%, p=0.118) between patients in the rescue therapy and control groups. Conclusion: In patients with ELVO with underlying ICAS requiring rescue therapy, despite longer procedural time and lower rate of first pass revascularization, rescue therapy appears to be safe with similar rate of favorable long-term functional outcomes compared to patients with large vessel occlusion from embolic source. Disclosures: S. Al Kasab: None. E. Almallouhi: None. I. Maier: None. A. Arthur: None. J. Kim: None. R. De Leacy: None. A. Rai: None. S. Keyrouz: None. K. Fargen: None. T. Dumont: None. P. Kan: None. R. Starke: None. A. Spiotta: None.